Analysis of Principal Leadership in the Social 5.0 Era: An Islamic Human Resource Management Perspective - Zainal Abidin; Hermansyah; Rony Syafriansyah; Syahrial Shaddiq; Khuzaini (International Journal Of Economics Social And Technology, 2025)
The world of education, especially in elementary schools, faces new challenges during the Society 5.0 era. As technology and digitalization advance, principals must be adaptable, innovative, and humane. This analysis discusses how Islamic Human Resource Management (IHRM) principles can be optimized for principal leadership in the Society 5.0 era. IHRM offers a relevant approach to building leadership that is not only professional but also grounded in Islamic values. By definition, Society 5.0 is a human-centered society based on advanced technologies such as artificial intelligence, the Internet of Things, and big data. To implement these era-era values ​​in elementary schools, educators must lead the digital transformation without neglecting the psychological, moral, and social needs of teachers and students. In other words, technology should not replace essential human interaction, but should be used to facilitate the educational process. According to IHRM, leadership is a combination of management skills with Islamic values ​​such as justice (al-'adl), trustworthiness, ihsan, and deliberation (shura). As leaders, principals have a moral responsibility to create an educational environment that is just, honest, and fosters a sense of solidarity. To maintain a balance between the application of technology and the development of students' character, these values ​​are important.